Effect of Phytase on Ileal Amino Acid Digestibility, Nitrogen Retention and AMEn for Broilers Fed Diets Containing Low and High Phytate Phosphorus - Manangi, M.K.; Sands, J.S.; Coon, C.N. (International Journal of Poultry Science, 2009)
A 42 d broiler experiment was conducted to determine the effect of added Escherichia coli phytase (Phyzyme-XP 5000G) to low and high phytate P (PP) diets on performance and nutrient digestibility. The experiment consisted of 12 treatments with 2 levels of PP: Low-Phytate (LP) group-0.24% and High-Phytate (HP) group-0.32%. Both LP and HP groups had respective Positive Controls (PCs) with 0.39% in the starter and 0.29% NPP in the grower, respectively and 5 basal diets with graded levels (0, 250, 500, 750 and 1000 FTU’s/kg diet) of added phytase. The HP diets contained additional PP because canola and rice bran were substituted for part of the corn and soybean meal. GE retention was significantly improved 6% percentage points for 42 d broilers fed either LP or HP diets with added phytase however a significant interaction indicated the improvement in energy retention caused by phytase was primarily from the broilers fed the HP diet. Overall there was no significant main effect of phytase on GE retention of 21 d broilers but the energy retention of HP diet was significantly less than for LP fed broilers and broilers fed the LP diet showed a significant improvement an interaction suggested the phytase would only benefit broilers fed the LP diet. The ileal % digestibility of threonine, tryptophan and serine were affected by PP levels, phytase and the interaction of PP and phytase for 21 d broilers, whereas cystine was the only amino acid to show all three main effects for 42 d broilers. In general, the interaction of phytase and PP for ileal digestibility of specific amino acids was caused by a lack of positive response of phytase when added to the HP diet for 21 d broilers, whereas phytase showed an influential trend of improving ileal digestibility of all amino acids (p = 0.1284) in either of the HP or LP diets for the older 42 d broiler. The slight improvement of ileal digestible amino acids seemed to correlate with a 6.2 percentage point improvement in % ileal N digestibility for 42 d broilers fed either the LP or HP diets. Broilers fed the LP PC diet had a higher % ileal nitrogen and energy digestion than broilers fed the HP PC diet at 21 d but there was no difference in 42 d broilers fed the two different PP diets. In summary adding phytase to broiler diets improved energy utilization by 2.1-4.9% for both LP and HP fed broilers and an 1.9-6.1% improved ileal % tAA digestibility for LP fed broilers.